1988
DOI: 10.1357/002224088785113720
|View full text |Cite
|
Sign up to set email alerts
|

Copepods in Fram Strait in summer: Distribution, feeding and metabolism

Abstract: A summer study of zooplankton in the Fram Strait area of the Greenland Sea showed elevated abundances of herbivorous copepods in the marginal ice zone or ice-edge compared with copepod communities under the pack ice cover. Several physical factors contributed to this, including the large-scale current systems which deliver both North Atlantic and Arctic plankton to the ice-edge and the effect of melting ice and eddies in increasing primary productivity and standing stocks of phytoplankton. The potential import… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

1988
1988
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(31 citation statements)
references
References 44 publications
2
29
0
Order By: Relevance
“…The high-resolution sections in the present study did not extend deep enough to detect the structure of the eddy; however, the analysis of fulldepth hydrographic point measurements, carried out in parallel to the continuous survey, confirmed the oc currence of a mesoscale anticyclonic baroclinic eddy, extending down to approximately 700 m (WSC slope section). Eddies can extend to depths greater than 500 m (Smith 1988), but the most pronounced contrasts in temperature are mostly found in the upper 25−50 m, as in cyclonic eddies in the Fram Strait (Johannessen et al 1987). The eddy observed in the present survey reached a diameter of approximately 30 km, which is a typical size for mesoscale eddies in the Fram Strait (Walczowski 2013), where the Rossby radius of deformation is on the order of 10 km.…”
Section: Discussionmentioning
confidence: 43%
“…The high-resolution sections in the present study did not extend deep enough to detect the structure of the eddy; however, the analysis of fulldepth hydrographic point measurements, carried out in parallel to the continuous survey, confirmed the oc currence of a mesoscale anticyclonic baroclinic eddy, extending down to approximately 700 m (WSC slope section). Eddies can extend to depths greater than 500 m (Smith 1988), but the most pronounced contrasts in temperature are mostly found in the upper 25−50 m, as in cyclonic eddies in the Fram Strait (Johannessen et al 1987). The eddy observed in the present survey reached a diameter of approximately 30 km, which is a typical size for mesoscale eddies in the Fram Strait (Walczowski 2013), where the Rossby radius of deformation is on the order of 10 km.…”
Section: Discussionmentioning
confidence: 43%
“…These populations did not undergo vertical migration (Smith 1988). In summer 1984 elevated concentrations of pheophyhn a and a high percentage of microflagellates w e r e observed in t h e ice e d g e zone i n Fram Strait (Smith e t al.…”
Section: Resultsmentioning
confidence: 99%
“…The influence of sea ice cover on zooplankton is complex, species specific, and differs among regions and seasonals. Smith (1988) concluded that in summer in Fram Strait, the ice edge had a positive effect on herbivorous zooplankton abundances because of elevated concentrations of plant biomass. However, Hirche et al (1991) did not find any enhanced biological activities along the ice edge in Fram Strait during the same season, although he mentioned considerable regional variability related to physical mesoscale processes.…”
Section: Discussionmentioning
confidence: 99%